Impact of IUD Counseling Educational Video on Third Trimester Pregnant Women's Knowledge and Readiness to Use Intrauterine Contraceptives - Harnaningsih Harnaningsih; Burhanuddin Bahar; Elizabet C. Jusuf; Sri Wahyuni Bahrum (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Family planning initiatives can improve the health of women by reducing the number of unintended or high-risk pregnancies. Look into potential locations: Generally speaking, the analyst at the Paccerakkang Community Wellness Center must examine the influence of educational counseling videos on the availability of information and the use of IUDs in third-trimester pregnant women. Thirty pregnant women in their third trimester made up the population in this study. The Whole Examining process was used to choose the inquiry exam. The measuring tool/instrument in this study was a survey about IUD counseling, educational videos about information and status of the use of IUDs in third-trimester pregnant women.  This investigation used univariate and bivariate tests, including the Mann Whitney autonomous test t test, which initially attempted to determine if the data was ordinarily distributed. The results of assessing knowledge both before and after receiving instruction within the framework of recordings produced a statistically significant value of 0,003 (p-value<0,05), while the results of assessing the availability of research subjects both before and after instruction produced a statistically significant value of 0,000 (p-value<0,05).  The findings of these two study tests indicate that IUD counseling training in the form of videos has an effect on third trimester pregnant women's knowledge and decision to use IUDs. The Paccerakkang Makassar Community Wellbeing Center's third trimester pregnant women's knowledge and availability to use IUDs are impacted by educational counseling videos, according to the center's findings.